The Application of Drip Irrigation Technique and Artificial Planting Media in the Cultivation of Lettuce (Lactuca sativa) - Mechram, Siti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The effort to develop artificial planting media and technique for more practical irrigation in the cities growing since the area of land available for farming is getting less. A glass house experiment was run to compare the performance of three types of planting media, i.e. 100% rice husk charcoal (RHC), a mixture of RHC (50%) and andosol (50%) and 100% andosol, which was watered in periodical (once a day, once in two days and once in three days respectively) by means of drip irrigation technique. A weekly observation were made on plant growth parameters (plant height, number of leaves, wide, length and the area of leaves) and the shoot length. A daily observation was performed for the room temperature (in the morning, noon and afternoon) and amount of water needed for irrigation. The plant was harvested after 31 days and the yield was determined by gravimetry method for fresh vegetable and in a dry form. The result showed that the use of a mixture between RHC (50%) and 50% andosol watered once ion two days gave the best plant growth and production yield. Â Keywords: Planting Media, watering interval, lettuce, drip irrigation